Soluble CLEC-2 as an Emerging Biomarker of In Vivo Platelet Activation - Katsue Suzuki-Inoue; Makyo Ueda; Toshiaki Shirai; Nagaharu Tsukiji; Tomoyuki Sasaki (Journal of Clinical Medicine, 2026)
Platelet activation plays a central role in arterial thrombosis, thromboinflammation, and microvascular injury. Conventional platelet function tests evaluate platelet responsiveness to exogenous agonists ex vivo but do not directly reflect in vivo platelet activation. Although several soluble platelet-derived molecules, including platelet factor 4 (PF4), β-thromboglobulin (β-TG), soluble P-selectin, soluble CD40 ligand, glycocalicin, and soluble glycoprotein (GP) VI, have been investigated as in vivo platelet activation markers, their clinical use is limited by preanalytical instability, lack of platelet specificity, constitutive shedding, or uncertain disease specificity. Soluble C-type lectin-like receptor 2 (sCLEC-2) has recently emerged as a promising biomarker of in vivo platelet activation. CLEC-2 is expressed predominantly in platelets and megakaryocytes, and its soluble form is released from activated platelets as both a shed molecule and a microparticle-associated form. Compared with PF4 and β-TG, sCLEC-2 is less susceptible to artifactual release during routine blood collection, making it more suitable for clinical laboratory testing. Elevated sCLEC-2 levels have been reported in acute coronary syndrome, acute ischemic stroke, disseminated intravascular coagulation, thrombotic microangiopathy, antiphospholipid antibody syndrome, and coronavirus disease 2019 (COVID-19). In thrombocytopenic disorders, indices incorporating platelet count, such as the C2PAC index, sCLEC-2/D-dimer ratio, and sCLEC-2 × D-dimer/platelet count, may better reflect platelet activation and disease status than sCLEC-2 concentration alone. However, preanalytical standardization, assay harmonization, reference interval validation, and disease-specific cutoff values remain essential. This review summarizes the biological basis, assay systems, clinical evidence, and future perspectives of sCLEC-2 as an emerging laboratory marker of in vivo platelet activation.